Direct isotopic evidence of biogenic methane production and efflux from beneath a temperate glacier. Issue 1 (December 2018) - Burns, R.; Wynn, P.; Barker, P.; McNamara, N.; Oakley, S.; Ostle, N.; Stott, A.; Tuffen, H.; Zhou, Zheng; Tweed, F.; Chesler, A.; Stuart, M.
Abstract The base of glaciers and ice sheets provide environments suitable for the production of methane. High pressure conditions beneath the impermeable 'cap' of overlying ice promote entrapment of methane reserves that can be released to the atmosphere during ice thinning and meltwater evacuation. However, contemporary glaciers and ice sheets are rarely accounted for as methane contributors through field measurements. Here, we present direct field-based evidence of methane production and release from beneath the Icelandic glacier Sólheimajökull, where geothermal activity creates sub-oxic conditions suited to methane production and preservation along the meltwater flow path. Methane production at the glacier bed (48 tonnes per day, or 39 mM CH4 m−2 day−1 ), and evasion to the atmosphere from the proglacial stream (41 tonnes per day, or 32 M CH4 m−2 day−1 ) indicates considerable production and release to the atmosphere during the summer melt season. Isotopic signatures (−60.2‰ to −7.6‰ for δ13 Cch 4 and −324.3‰ to +161.1‰ for Dch 4 ), support a biogenic signature within waters emerging from the subglacial environment. Temperate glacial methane production and release may thus be a significant and hitherto unresolved contributor of a potent greenhouse gas to the atmosphere.